PENGARUH LEVERAGE, KEPEMILIKAN INSTITUSIONAL, DAN KUALITAS AUDIT DALAM PENGHINDARAN PAJAK PADA PERUSAHAAN SEKTOR INDUSTRI YANG TERDAFTAR DI BURSA EFEK INDONESIA - Widya Astuti; Caterina Lo; Ivo Gismi Lestari (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
This study was conducted to analyze the effect of the Leverage, Ownership Institutional and Quality Audit on the Tax Avoidance (CETR) of manufacturing companies in the industrial sector listed on Indonesia Stock Exchange for the Period 2017 - 2020 either partially or simultaneously. The sampling method is purposive sampling. The number of samples used in this study were 21 industrial companies listed on the Indonesia Stock Exchange (IDX) from a total population of 42 companies. The type of data used is secondary data sourced from financial statement data and annual reports of each company. The data analysis method used in this study uses multiple linear regression analysis techniques. As a result of the survey, leverage has a positive and significant impact on partial tax avoidance, and the quality of institutional ownership and audits of the industrial sector listed on the Indonesia Stock Exchange between 2017 - 2020. We conclude that it does not have a significant negative impact on the partial tax avoidance of companies. High levels indicate corporate tax avoidance practices, low institutional ownership proves that the number of corporate controls and public ownership remains dominant, and audit quality is corporate tax avoidance practices at the time of audit.